The Mindful Self: A Mindfulness-Enlightened Self-view - Xiao, Qianguo; Yue, Caizhen; He, Weijie; Yu, Jia-yuan (Frontiers in psychology, 2017)
This paper analyzes studies of mindfulness and the self, with the aim of deepening our understanding of the potential benefits of mindfulness and meditation for mental health and well-being. Our review of empirical research reveals that positive changes in attitudes toward the self and others as a result of mindfulness-enabled practices can play an important role in modulating many mental and physical health problems. Accordingly, we introduce a new concept-the "mindful self"-and compare it with related psychological constructs to describe the positive changes in self-attitude associated with mindfulness meditation practices or interventions. The mindful self is conceptualized as a mindfulness-enlightened self-view and attitude developed by internalizing and integrating the essence of Buddhist psychology into one's self-system. We further posit that the mindful self will be an important intermediary between mindfulness intervention and mental health problems, and an important moderator in promoting well-being. More generally, we suggest that the mindful self may also be an applicable concept with which to describe and predict the higher level of self-development of those who grow up in the culture of Buddhism or regularly engage in meditation over a long period of time.